The preferences of tourists in their expectations of chateau gardens: a Central and Eastern European perspective. Issue 4 (1st October 2016) - Navrátil, Josef; Kučera, Tomáš; Pícha, Kamil; White Baravalle Gilliam, Vivian L.; Havlíková, Gabriela
Abstract : As most of the chateau gardens and parks in Central and Eastern Europe have been neglected or misused, there is a strong need for their transformation. This transformation has become even more important now due to the growing competition in the tourist destination market. The chateau gardens are at the crossroads of choosing the variant of their future development. Tourism of this kind is able to maintain its original features and it can also find new commercial uses. The aim of this paper is to identify the demand segments and to assess the relation of the visitors to the elements that form the character of a chateau park. We have succeeded in identifying three motivating factors for tourists in the making their choice. While some types of use are mutually complementary (knowledge and relaxation), other types are not used as much (amusement). The introduction of an entrance fee implies that there will be a change in the preference for those parks with the presence of peacocks and ducks, as well as the outdoor collections of plants including both French and English style gardens and they are equipped with detailed information board.